Media Sosial dan Perubahan Pola Belajar Gen Z dalam Pendidikan Islam - Lailatul Khoiriyah; Ludziatul A’yuni; Kamila Nur Annisa; Jakaria Umro (Journal of Islamic Education and Learning, 2026)
The development of social media has significantly transformed the learning patterns of Generation Z, including within the context of Islamic education. Social media functions not only as a communication tool but also as a primary source for accessing Islamic knowledge quickly and widely. This phenomenon has shifted learning patterns from conventional approaches to more flexible, visual, and instant digital learning. This study aims to analyze how social media influences the changes in Gen Z’s learning patterns and its implications for Islamic education. The research employs a library research method by reviewing various scholarly literatures related to sociology of education, digital culture, and Islamic learning in the era of social media. The findings reveal that social media encourages more independent, adaptive, and need-based learning patterns, yet tends to promote superficial and fragmented understanding. Additionally, there is a shift in knowledge authority from formal institutions to popular figures on social media. In the context of Islamic education, this raises challenges in maintaining depth of understanding and scholarly authority. In conclusion, social media plays a significant role in transforming Gen Z’s learning patterns, requiring adaptive learning strategies that preserve the essential values of Islamic education.